Legal Advisory About The Dangers Of Hoax News For Millenial Generations In Madrasah Aliyah Negeri I Probolinggo - Mushafi; Faridy (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
This community service is packed with legal counseling with the theme "the danger of hoax news for the millennial generation. This is because the millennial generation is a generation that is very vulnerable to being affected by hoax news. The millennial generation is the generation that has broad access to social media. Almost every time they will interact with Social Media which contains a lot of hoax information. On this basis, it is important to carry out legal counseling for students of MAN 1 Probilinggo who are part of the millennial generation.